ANALISIS KEPUASAN KONSUMEN TERHADAP LAYANAN KERETA API JARAK JAUH PT. KERETA API INDONESIA (PERSERO) BERDASARKAN MARKETING MIX 5P DI DAERAH OPERASI 1 JAKARTA - Tansah Bagas Prakosa Jati; Yenita (GoAcademica Research dan Publishing, 2023)
Train is a land transportation mode that is quite reliable and environmentally friendly and has advantages that other land transportation modes do not have, namely in terms of carrying capacity and punctuality of travel. The advantages of rail transportation have been used for centuries as a means of delivering passengers and goods with a destination that can be directly entered in the city center. PT. Kereta Api Indonesia (Persero) is a transportation provider that provides this train transportation service, one of whose services is the Long-Distance Train service managed by the Jakarta Operational Area 1 for departure from Jakarta to major cities throughout the island of Java which is affordable to the railway network. The advantages of the train mode make this mode excellent for service users who want to travel out of the city from the city of Jakarta, However, being the main choice of service users makes transportation operators continue to improve services and improve services to service users on an ongoing basis. To see further how the improvement of services is carried out, the concept of marketing mix involving promotional variables, places, people, physical environment and processes analyzed with the SPSS program is used so that mathematical conclusions are obtained to interpret the factors that affect consumer satisfaction from the 5 variables of the marketing mix concept. In this study, it was found that the physical environment variable has the greatest influence on consumer satisfaction which is then followed by physical environmental factors, processes, promotions, places, and people.